Current perspectives and trend of ferroptosis in head and neck cancer: a bibliometric analysis - Pan, Jin; Zhang, Yi; Zhao, Binbin; Shao, Wei; Chen, Xin (Frontiers in Oral Health, 2025)
BackgroundFerroptosis, a form of regulated cell death driven by iron dependency, is also referred to as iron-mediated cell death. In recent years, ferroptosis has garnered considerable research interest as a distinct cell death mechanism, primarily characterized by excessive intracellular iron accumulation and the formation of lipid peroxides. Ferroptosis is intricately linked to the initiation and progression of a wide spectrum of diseases, notably cancers, neurodegenerative disorders—including Alzheimer's and Parkinson's diseases—and cardiovascular conditions. Despite growing interest in ferroptosis within cancer research, systematic analyses and comprehensive visualizations of research hotspots, leading contributors, and emerging trends—particularly in the context of head and neck cancers—remain limited.Materials and methodsThis study conducted a bibliometric analysis using data retrieved from the Web of Science Core Collection, covering the period from January 1, 2016, to March 20, 2025. Bibliometric mapping and visualization were performed using VOSviewer and CiteSpace.ResultsA total of 110 publications were identified across 19 countries. China contributed the highest number of publications (84 articles; 76.36%), followed by South Korea (14 articles; 12.73%) and the United States (6 articles; 5.46%). Nature, Cell, and Cancer Letters emerged as the leading academic journals publishing on ferroptosis in the context of head and neck cancers. Emerging high-frequency keywords—such as “expression” “cell death” “ferroptosis” “inhibition” “metabolism” and “therapy”—highlight evolving research frontiers in this field.ConclusionThis study presents a comprehensive overview of recent trends and advances in ferroptosis research within the context of head and neck cancer, delineating key research frontiers and emerging thematic areas. The findings offer valuable insights and serve as a useful reference for researchers pursuing work in this domain.